Profilaxia intermitente na convulsão febril com diazepam via oral Intermittent prophylaxis in febrile seizures with oral diazepam - Marilisa M. Guerreiro; Maristela Costa; M. Angela Bellomo; Sílvia H. Sabino; Ednéa A. Silva; Anna E. Scotoni (Arquivos de Neuro-Psiquiatria)
Apresentamos a profilaxia intermitente com diazepam via oral como opção de tratamento para convulsão febril. Justificamos essa proposta diante dos importantes efeitos colaterais que ocorrem com as duas medicações classicamente usadas na profilaxia contínua (fenobarbital e valproato). Foram tratados 19 pacientes. Obtivemos resultados favoráveis, pois apenas um caso apresentou recorrência de convulsão febril em vigência de dose adequada do diazepam. Houve efeitos colaterais transitórios em 36,8% da nossa casuística. Intermittent prophylaxis with oral diazepam is presented as an optional treatment for febrile seizures. This proposition is justified by the severe side effects of the currently used chronic anticonvulsant drug therapy in febrile seizures (phenobarbital and valproate). Nineteen patients aged between 3 months and 5 years were treated. They had either simple) or complex febrile seizures. Sixteen patients, had at least one prognostic factor for recurrence of febrile seizures: first febrile seizure before 15 months of age, positive family history for epilepsy or febrile seizures, occurrence of a complex febrile seizure or abnormal neurological examination. Three patients had none, (cases 8, 12 and 13). We recommended 2.5mg b.i.d. for children younger than 12 months, 5mg b.i.d. for children older than 12 months and younger than 3 years, and 7.5 b.i.d. for children older than 3 years. The results showed that only one patient had febrile convulsions while taking adequate diazepam dosage. Transient side effects occurred in 36.8% of the cases.